Functional, bioactive, and sensory properties of nutraceutical beverages enriched with passion fruit (Passiflora edulis) peel fiber - David Betancur-Ancona; Cecilia Pérez-Navarrete; Luis Chel-Guerrero; Irving Sosa-Crespo; ValentinoMukthar Sandoval-Peraza (Food Chemistry Advances)
Passion fruit (Passiflora edulis) is industrially processed to obtain pulp and juice, generating large quantities of peel as waste. With proper treatment, it could be turned into a by-product with functional or nutraceutical properties, with health benefits for the consumer. In this study, the functional and bioactive properties of the passion fruit fiber-rich fraction (PfFRF) obtained from the fruit peel was determined and subsequently incorporated in the preparation of a passion fruit flavored powdered beverage (PfFPB) and a hibiscus flavored powdered beverage (HFPB). The proximate composition, functional, biological, and sensory acceptance properties of these formulations, were determined and compared with a control (Metamucil, MC). Total dietary fiber (TDF) was the major component for PfFPB and HFPB (52.16 and 46.62 %, respectively). Functional properties revealed that both formulations showed water and oil holding capacity (about 400 and 200 %, respectively), with an emulsifying capacity of about 50 % and a 100 % stability. Biological properties showed that PfFPB and HFPB presented the ability to uptake organic molecules by about 30 %. Both formulations had better functional and biological properties compared to MC, with the exception of water holding capacity. In the sensory evaluation, PfFPB and HFPB ranked between I neither like it nor dislike it and I like it little on average, unlike MC, which was rejected. For the attribute’s appearance, texture, and taste PfFPB and HFPB were better than MC, while for the aroma attribute there we no differences detected between samples. This data suggests that PfFRF-added beverages may be an adjuvant against various chronic degenerative diseases.